Can triad forestry reconcile Europe’s biodiversity and forestry strategies? A critical evaluation of forest zoning - Thomas A. Nagel; Mariano Rodríguez-Recio; Tuomas Aakala; Per Angelstam; Admir Avdagić; Zbigniew Borowski; Andrés Bravo-Oviedo; Gediminas Brazaitis; Thomas Campagnaro; Michał Ciach; Milic Curovic; Inken Doerfler; et al. (Ambio, 2025)
Balancing increasing demand for wood products while also maintaining forest biodiversity is a paramount challenge. Europe’s Biodiversity and Forest Strategies for 2030 attempt to address this challenge. Together, they call for strict protection of 10% of land area, including all primary and old growth forests, increasing use of ecological forestry, and less reliance on monocultural plantations. Using data on country wide silvicultural practices and a new database on strict forest reserves across Europe, we assess how triad forest zoning could help meet these goals. Our analysis reveals that zoning in Europe is overwhelmingly focused on wood production, while there has been little concomitant protection of forests in strict reserves. Moreover, most strict forest reserves are